Students’ Perceptions and Experiences of Using Google Translate as a Supporting Media in Learning Vocabulary at Senior High School - Fikni, Zahratul; Usuluddin; Juliani; Wati, Laila (LITPAM, 2026)
This study aims to identify students' perceptions and experiences in using Google Translate as an English vocabulary learning tool at SMK Islam Islahul Ummah NWDI Anggaraksa. This study used a qualitative descriptive approach, with data collected through a Likert-scale questionnaire, semi-structured interviews, and documentation. Participants in this study were 15 10th-grade Management students who completed the questionnaire and 5 informants selected through purposive sampling for interviews. The questionnaire results showed that students' overall perceptions of the use of Google Translate fell into the